2018
DOI: 10.2118/184880-pa
|View full text |Cite
|
Sign up to set email alerts
|

Far-Field Proppant Detection Using Electromagnetic Methods: Latest Field Results

Abstract: Summary More than 100 billion lbm of proppant are placed annually in wells across the globe, with the majority in unconventional reservoirs. The location of the proppant in these horizontal wells and formations is critical to understanding reservoir drainage, well spacing, and stage spacing. However, for many years proppant detection has primarily been limited to near-wellbore measurements. A novel method to detect proppant in the far field has been developed and is the subject of this paper. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…It is observed that the relative change of the magnetic field is about two orders larger than that of the electric field. This observation is consistent with that observed in the field experiment . The change in surface response promises to provide an economical way to monitor fracturing in deep subsurface regions.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is observed that the relative change of the magnetic field is about two orders larger than that of the electric field. This observation is consistent with that observed in the field experiment . The change in surface response promises to provide an economical way to monitor fracturing in deep subsurface regions.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…This observation is consistent with that observed in the field experiment. 40 The change in surface response promises to provide an economical way to monitor fracturing in deep subsurface regions.…”
Section: Near-surface Monitoring Of Hydraulic Fracturesmentioning
confidence: 99%
“…• Subsurface detection technique for tracking proppants (Palisch et al, 2017) can be used for calibrating the proppant transport modelling in field problems.…”
Section: Recommendations For Future Workmentioning
confidence: 99%
“…As the oil gets depleted and the anomalous (light blue) zone approaches the producer well, a non-zero Bx and Bz emerge, which can be analyzed to determine the distance to the waterfront. Further applications include monitoring hydraulic fracturing which is one of the next frontiers, and EM is surprisingly effective in this (Palish et al 2017). Note that the electric field shows mostly early-time anomaly, while the magnetic field always displays anomalous response.…”
Section: Figure 14mentioning
confidence: 99%